2017
DOI: 10.1111/joic.12421
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐loading therapy with statins in patients with angina and acute coronary syndromes undergoing PCI

Abstract: Statins constitute the most powerful class of drugs for cardiovascular risk reduction associated to atherosclerosis. Their important pharmacological properties include reduction of serum lipid concentrations and non-lipid related, pleotropic effects such as anti-inflammatory action. Previous largescale randomized studies have demonstrated the beneficial effects of statin loading prior to elective percutaneous coronary intervention (PCI) for the reduction of periprocedural myocardial infarction and prevention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…These effects include preserving endothelial function, stabilizing arterial plaque, scavenging free radicals, and inhibiting proliferation, inflammation, and apoptosis [8]. A meta-analysis of 13 randomized studies showed statin pre-treatment was associated with reduced peri-procedural myocardial infarction and a 44% risk reduction in major adverse cardiovascular events at 30-d irrespective of clinical presentation [9], and similar findings were also found in recent studies [10,11]. The American College of Cardiology, American Heart Association, and European Society of Cardiology have suggested that statins should be used as the secondary prevention following acute myocardial infarction (AMI).…”
Section: Introductionsupporting
confidence: 53%
“…These effects include preserving endothelial function, stabilizing arterial plaque, scavenging free radicals, and inhibiting proliferation, inflammation, and apoptosis [8]. A meta-analysis of 13 randomized studies showed statin pre-treatment was associated with reduced peri-procedural myocardial infarction and a 44% risk reduction in major adverse cardiovascular events at 30-d irrespective of clinical presentation [9], and similar findings were also found in recent studies [10,11]. The American College of Cardiology, American Heart Association, and European Society of Cardiology have suggested that statins should be used as the secondary prevention following acute myocardial infarction (AMI).…”
Section: Introductionsupporting
confidence: 53%
“…A study with rosuvastatin loading in the elderly with an ACS that had a PCI can attenuate the increase in hsCRP, CK-MB, and cTnI, decrease myocardial injury and inflammatory reaction caused by PCI, and improve left ventricular function 30 days after PCI [ 72 ]. Similar were the effects of all potent statins [ 73 ]. Moreover, in patients that undergo PCI, statin therapy is effective at reducing the risk of contrast-induced acute kidney injury and its short- mid- long-term adverse effects related to CVD events [ 74 - 77 ].…”
Section: Greace Atorvastatin and Coronary Heart Disease Evaluation (Gmentioning
confidence: 76%
“…Additional basic science studies are needed to better elucidate the underlying molecular mechanisms through which trimetazidine exerts its actions. Thirdly, given the benefit of statin pretreatment for patients with stable angina and acute coronary syndrome undergoing PCI [31], future studies can explore the potential synergistic effects of trimetazidine and statin pretreatment in this patient population. Fourthly, we did not conduct a subgroup analysis according to TIMI flow restoration and thrombus burden, which might also have effect on endothelial damage and myocardial injury.…”
Section: Discussionmentioning
confidence: 99%